2018
DOI: 10.1103/physrevb.98.235406
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying wave-function overlaps in inhomogeneous Majorana nanowires

Abstract: A key property of Majorana zero modes is their protection against local perturbations. In the standard picture, this protection is guaranteed by a high degree of spatial nonlocality of the Majoranas, namely a suppressed wave-function overlap, in the topological phase. However, a careful characterisation of resilience to local noise goes beyond mere spatial separation, and must also take into account the projection of wave-function spin. By considering the susceptibility of a given zero mode to different local … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 71 publications
4
80
0
Order By: Relevance
“…We nevertheless argue that one can compellingly distinguish the two scenarios in a single prototype qubit at fixed L by carrying out the protocol at different field strengths B. Numerous numerical simulations [23,24,26,28,29,31] indicate a tendency for low-energy Andreev bound states to form over an extended field interval below the onset of a topological phase hosting true Majorana zero modes. In such a scenario, upon increasing B from zero, the system first realizes an ABS qubit, then encounters a topological phase transition at a critical field B c , and finally forms a topological qubit.…”
Section: Executive Summarymentioning
confidence: 93%
“…We nevertheless argue that one can compellingly distinguish the two scenarios in a single prototype qubit at fixed L by carrying out the protocol at different field strengths B. Numerous numerical simulations [23,24,26,28,29,31] indicate a tendency for low-energy Andreev bound states to form over an extended field interval below the onset of a topological phase hosting true Majorana zero modes. In such a scenario, upon increasing B from zero, the system first realizes an ABS qubit, then encounters a topological phase transition at a critical field B c , and finally forms a topological qubit.…”
Section: Executive Summarymentioning
confidence: 93%
“…However, in the last couple of years it has been shown that the electrostatic environment and the three-dimensionality of these wires play an important role in all aspects concern-ing the trivial/topological phases and the appearance of MBSs. For instance, the electrostatic profile is not homogeneous along (and across) the wire, which creates a position-dependent chemical potential 23,24,26,[41][42][43] that has consequences for the topological phase transition and the shape and the overlap of MBSs [44][45][46][47] . It also creates a position-dependent Rashba spin-orbit coupling [48][49][50] .…”
Section: Introductionmentioning
confidence: 99%
“…7(a)]. Consequence of such overlapping wavefunctions have been studied by a num- ber of authors [67][68][69]. In some analogy to this behaviour, also variation of the plaquette size N x × N y can lead to rearrangement of the quasiparticle states, depending on µ 2D .…”
Section: B Plaquette-nanowire Hybridmentioning
confidence: 97%